Agronomic performance of common bean in straw mulch systems and topdressing nitrogen rates in no-tillage - Cunha, Tatiana Pagan Loeiro Da (2015)
ABSTRACTIn no-tillage systems, straw coverage on soil surface is the key to success, and the choice of crops for rotation is crucial to achieve the sustainability and quality that conservation agriculture requires. The objective of this study was to evaluate the agronomic performance of the common bean cultivar IAC Formoso sown in succession to three straw mulch systems (corn alone, corn/Urochloa ruziziensisintercrop and U. ruziziensisalone) and topdress nitrogen rates (0; 40; 80; 120 and 160 kg ha-1N), at the four-leaf stage, three years after the implementation of no-tillage. The experiment was arranged in a randomized block split plot design, with three replications. Common bean highest yields were achieved in succession to U. ruziziensisalone and intercropped with corn. The corn/U. ruziziensisintercrop provided both straw and seed production, allowing for quality no-tillage. Topdressed nitrogen influenced the common bean yield when in succession to corn alone, U. ruziziensisalone and corn/U. ruziziensisintercrop in no-tillage.